The white-coat effect is an independent predictor of myocardial ischemia in resistant hypertension. (October 2014) - Modolo, Rodrigo; Ruggeri Barbaro, Natália; de Faria, Ana Paula; Rodrigues Sabbatini, Andréa; Paganelli, Maria Ondina; Fontana, Vanessa; Moreno, Heitor
Abstract White-coat hypertension (WCH), commonly found in pseudoresistant hypertension, does not pose higher cardiovascular risk than hypertensive status. However, when the decrease of the out-of-office blood pressure does not reach normal levels – the white-coat effect (WCE) – the repercussions are still obscure. We investigated the repercussions of the WCE in myocardial perfusion in resistant hypertension (RHTN). We enrolled 129 asymptomatic RHTN subjects – divided into WCE (n = 63) and non-WCE (n = 66) – to perform rest and stress myocardial perfusion scintigraphy and biochemical tests. Groups were equal regarding age, gender and body mass index. There was a high prevalence of WCE (49%). WCE was associated with higher prevalence of myocardial ischemia (49.2% vs 7.6%, p < 0.001), microalbuminuria (60.3% vs 36.4%, p = 0.01) and higher heart rate (72 [64–80] vs 64 [60–69], p < 0.001), compared with non-WCE patients. On an adjusted logistic regression, heart rate was considered a predictor of WCE (OR = 1.10, 95% CI 1.04–1.15; p < 0.001), but not MA (OR = 1.8, 95% CI 0.8–3.9; p = 0.15). On a second model of adjusted logistic regression, WCE was an independent predictor of myocardial ischemia (OR = 14.7, 95% CI 4.8–44.8; p < 0.001). We found a high prevalence of WCE in RHTN, and this effect may predict silent myocardial ischemia in this subset of hypertensive patients. In this group of hypertensives special attention should be given to the WCE.